Awareness, treatment, and control of hypertension among adult population in a rural community of Singur block, Hooghly District, West Bengal - Nabarun Karmakar; Kaushik Nag; Indranil Saha; Ramanathan Parthasarathi; Manas Patra; Rabindranath Sinha (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Hypertension is an important treatable public health problem both globally and in India with an increasing prevalence significantly in both urban and rural population. It is one of the leading causes of adult mortality and morbidity, but poorly controlled hypertension remains a major health problem. OBJECTIVE: The objective of this study was to find out awareness, treatment, and control of hypertension among study population and association of hypertension awareness with sociodemographic factors, if any. MATERIALS AND METHODS: This study was conducted from May 2013 to April 2014 in the rural community of Singur block, West Bengal. Data were collected with respect to sociodemographic characteristics as well as records related to hypertension such as awareness, treatment, and control of hypertension. Blood pressure (BP) measurement of individuals aged 20 years and above of both sexes was done. Pearson's Chi-square test was performed to find out the association between the categorical variables. SPSS 19.00 software was used for analysis. RESULTS: Nearly 48.2% of the participants were aware of their elevated BP; 47.1% of the participants were taking pharmacological treatment, mostly allopathic and only 8.8% had their BP under control. A statistically significant association was found between age, education, and socioeconomic status (per capita income) with awareness of hypertension. CONCLUSION: Lack of awareness of the disease and very low rate of control of hypertension among those who were treated became the major issues. These findings emphasize the need for dissemination of knowledge about the disease and counseling of the patients during treatment continuation.